Disentangling sequential and concerted fragmentations of molecular polycations with covariant native frame analysis. Issue 37 (15th September 2022) - McManus, Joseph W.; Walmsley, Tiffany; Nagaya, Kiyonobu; Harries, James R.; Kumagai, Yoshiaki; Iwayama, Hiroshi; Ashfold, Michael N.R.; Britton, Mathew; Bucksbaum, Philip H.; Downes-Ward, Briony; Driver, Taran; Heathcote, David; et al.
Abstract : Using covariance analysis methods, we study the fragmentation dynamics of multiply ionized 1- and 2-iodopropane. Signatures of isomer-specific nuclear motion occurring during sequential fragmentation pathways are identified. Abstract : We present results from an experimental ion imaging study into the fragmentation dynamics of 1-iodopropane and 2-iodopropane following interaction with extreme ultraviolet intense femtosecond laser pulses with a photon energy of 95 eV. Using covariance imaging analysis, a range of observed fragmentation pathways of the resulting polycations can be isolated and interrogated in detail at relatively high ion count rates (∼12 ions shot −1 ). By incorporating the recently developed native frames analysis approach into the three-dimensional covariance imaging procedure, contributions from three-body concerted and sequential fragmentation mechanisms can be isolated. The angular distribution of the fragment ions is much more complex than in previously reported studies for triatomic polycations, and differs substantially between the two isomeric species. With support of simple simulations of the dissociation channels of interest, detailed physical insights into the fragmentation dynamics are obtained, including how the initial dissociation step in a sequential mechanism influences rovibrational dynamics in the metastable intermediate ion and how signatures of this nuclear motion manifest in the measured signals.